Influence of Adrenalectomy on Protective Effects of Urocortin I, a Corticotropin-Releasing Factor, Against Indomethacin-Induced Enteropathy in Rats - Takeuchi, Koji; Abe, Naoko; Kumano, Aiko (Current Neuropharmacology, 2016)
We examined the influence of adrenalectomy on NSAID-induced small intestinal damage in rats and investigated the possible involvement of adrenal glucocorticoids in the protective effects of urocortin I, a corticotropin-releasing factor (CRF) agonist. Male SD rats without fasting were administered indomethacin s.c. and killed 24 h later in order to examine the hemorrhagic lesions that developed in the small intestine. Urocortin I (20 μg/kg) was given i.v. 10 min before the administration of indomethacin. Bilateral adrenalectomy was performed a week before the experiment. Indomethacin (10 mg/kg) caused multiple hemorrhagic lesions in the small intestine, which were accompanied by a decrease in mucus secretion and increases in intestinal motility, enterobacterial invasion, and iNOS expression. Adrenalectomy markedly increased the ulcerogenic and motility responses caused by indomethacin, with further enhancements in bacterial invasion and iNOS expression; severe lesions occurred at 3 mg/kg, a dose that did not induce any damage in sham-operated rats. This worsening effect was also observed by the pretreatment with mifepristone (a glucocorticoid receptor antagonist). Urocortin I prevented indomethacin-induced enteropathy, and this effect was completely abrogated by the pretreatment with astressin 2B, a CRF2 receptor antagonist, but was not significantly affected by either adrenalectomy or the mifepristone pretreatment. These results suggested that adrenalectomy aggravated the intestinal ulcerogenic response to indomethacin, the intestinal hypermotility response may be a key element in the mechanism for this aggravation, and endogenous glucocorticoids played a role in intestinal mucosal defense against indomethacin-induced enteropathy, but did not account for the protective effects of urocortin I, which were mediated by the activation of peripheral CRF2 receptors.
Keywords: CRF2R